PENINGKATAN HASIL BELAJAR MATA KULIAH BIOTEKNOLOGI MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) BERBASIS MEDIA AUDIO VISUAL DI KELAS PGMIPA-U PROGRAM STUDI PENDIDIKAN BIOLOGI FKIP UNIVERSITAS RIAU - Mahadi, Imam (Perspektif Pendidikan dan Keguruan, 2017)
Compentency is expected in biotechnology subjects learning requires student to make it more in learning. It requiresd a real effort both from lectures and from students. Class Action Research has been conducted (PTK), which aims to improve the activity and the results of studying Biotechnology with the type STAD cooperative learning based audio visual media in class of PGMIPA-U Biology FKIP UR. The result of data analysis cycle I and cycle II showed an increase in student learning activities for all indicator. The improvement of the student activity everage from I cycle about 69,46% up to II cycle about 89%. An increase in student activity 20.5%. Learning outcomes of students in I cycle and II cycle also increased. The average value of learning outcomes students increased from pre-cycle 71.35 to 75.55 in I cycle and then from I cycle 75.55 to 84.15 in II cycle. Generally its can be said that the use of cooperative learning model type STAD based Audio visual in biotechnology teaching can anhance students learning outcome.. Keywords: Cooperative Learning Model Type